Pelecehan Seksual Verbal (Catcalling) sebagai Tindak Pidana: Menuju Ruang Publik yang Aman bagi Perempuan dalam Perspektif KUHP dan TPKS - Salamah, Nur Hanifatus (Proceedings Series on Social Sciences & Humanities, 2024)
Criminal Code and the Penal Code for Sexual Violence, verbal sexual harassment, also known as catcalling, is considered a criminal offense. This kind of sexual harassment is common in public spaces, especially in Indonesia. This behavior not only makes women feel insecure and uncomfortable, but it can also lead to psychological trauma. This research is normative legal research or library research. The results showed and understood the legal framework related to verbal sexual harassment, also known as catcalling, in Indonesia. As well as raising public awareness of rights and law enforcement, in order to create a safe public environment for women, it can be concluded that the law enforcement of perpetrators of verbal sexual harassment (catcalling) still faces some problems. This includes low public awareness and a lack of solid evidence. To ensure legal certainty, there needs to be a new policy governing catcalling and social sanctions for perpetrators.